Design of a Rubbery Carboxymethyl Cellulose/Polyacrylic Acid Hydrogel via Visible‐Light‐Triggered Polymerization. Issue 6 (30th March 2017) - Zhu, Longxiang; Qiu, Jianhui; Sakai, Eiichi; Zang, Limin; Yu, Yanling; Ito, Kazushi; Liu, Peng; Kang, Feiyu
Abstract : A mesoscopic inhomogeneous hydrogel consisting of carboxymethyl cellulose (CMC) and polyacrylic acid is synthesized through a facile, one‐pot, visible‐light‐triggered polymerization. In this hydrogel, the curling CMC acts as initiator and cross‐linker. The hydrogel possesses an energy dissipation mechanism through the reversible deformation of curling CMC domains. The hydrogel exhibits a recovery time within 10 ms and over 92% resilience during impact and cyclic tensile tests, respectively. Abstract : Hydrogels, as soft and wet materials, have attracted great attention in the field of functional biomaterials. Most recently, the designed hydrogels, according to the energy dissipation principle, overcome the low mechanical strength, poor toughness, and limited recoverability of common hydrogels and show excellent mechanical properties. However, most of these novel designed hydrogels are lacking of instantaneous recovery and antifatigue properties. In this study, a mesoscopic inhomogeneous hydrogel consisting of carboxymethyl cellulose and polyacrylic acid is synthesized through a facile, one‐pot, visible‐light‐triggered polymerization. The prepared hydrogel can be stretched over 700% with fracture strength as high as 850 kPa, and shows a high elastic modulus (180 kPa). The microgel aggregated structure endows an efficient energy dissipation mechanism to the hydrogel. After the internal network structure stabilizing, the hydrogel exhibits a recovery time within 10 ms and over 92% resilience during impact and cyclic tensile tests, respectively. The hydrogel with such excellent mechanical properties can extend its application in biomaterial fields.